The Role of Core Competencies, Functional Competencies and Spiritual Competencies in Improving Teacher’s Teaching Quality at SD Nizamia Andalusia Jakarta - Subur, Jumadi (Sinergi International Journal of Management and Business, 2025)
This study investigated the influence of core, functional, and spiritual competencies on teachers' perceived teaching quality at SD Nizamia Andalusia Jakarta, an Islamic elementary school to examine the relationships between these competency dimensions and teaching quality. Data were collected through questionnaires administered to the entire teaching staff. The results confirmed that core, functional, and spiritual competencies collectively explained a substantial amount of the variance in perceived teaching quality among the teachers. Notably, the findings highlighted the interconnected importance of all three competency dimensions, with spiritual competencies emerging as a particularly influential factor within this specific Islamic educational context. This suggests that beyond fundamental and pedagogical skills, the embodiment of spiritual values significantly contributes to teachers' effectiveness and overall teaching quality within an Islamic school setting. The study highlights the need for comprehensive teacher development programs that address all three competency domains to enhance educational outcomes in Islamic elementary education.